DIVERSITY AS AN OPPORTUNITY AND CHALLENGE OF MODERN ORGANIZATIONS IN TSL AREA - Dagmara GOLBA; Katarzyna TUROŃ; Piotr CZECH (Scientific Journal of Silesian University of Technology. Series Transport, 2016)
Diversity management is a long-term process, which more and more attention to attach organizations in all industries, including in the area of TSL (Transport-Shipping-Logistics). The key is to notice and appreciate the differences between employees and understand that proper working conditions allow for optimal use of the potential of a diverse team. The article explains the concept of diversity and corporate social responsibility, and also presented the organization's approach from the TSL sector to diversity.